Sosialisasi Keselamatan dan Kesehatan Kerja untuk Meningkatkan Kinerja Karyawan pada Unit LDPM Gapoktan Sidomulyo - Eska Stefani; Artita Devi Maharani; Epsilandri Sepryarini (Universitas Widya Mataram, 2024)
Occupational Safety and Health (K3) aspects are one of the important factorsin creating a safe and productive work environment. Awareness of theimportance of K3 is still low among employees of the LDPM GapoktanSidomulyo Unit, which can increase the risk of work accidents and reduceproductivity. In addition, the inadequate availability and use of personalprotective equipment (PPE) increases vulnerability to work-related accidentsand diseases. This program aims to provide knowledge about K3, provideknowledge on how to identify potential hazards in the workplace and takesteps to prevent work accidents. This service is carried out through threepreparation stages, namely, implementation of K3 socialization, as well asevaluation and follow-up. The result of this service was that the K3 outreachactivities carried out by the UST service team succeeded in increasing theunderstanding of employees at the LDPM Gapoktan Sidomulyo Unit. Thisincrease has a positive impact on employee performance, by creating a safer,more productive and efficient work environment.